Genotype-Phenotype Correlation in Patients with Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency in Cuba - Tania Mayvel Espinosa Reyes; Teresa Collazo Mesa; Paulina Arasely Lantigua Cruz; Adriana Agramonte Machado; Emma Domínguez Alonso; Henrik Falhammar (International Journal of Endocrinology)
Background. There are several studies that show a good genotype-phenotype correlation in congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21OHD). However, there is well-documented evidence of inconsistency in some cases. Objectives. To determine if there is a correlation between the identified mutations and the clinical manifestations of 21OHD in the Cuban population. Methods. A cross-sectional descriptive study of all patients referred for a molecular diagnosis of 21OHD in Cuba from January 2000 to December 2018. The clinical manifestations of each patient were identified and classified according to the phenotype. The CYP21A2 gene was analyzed for the presence of 5 point mutations involved in the pathogenesis of 21OHD (intron 2, deletion of 8bp, I172N, P30L, and Q318X); correlation was sought between the phenotypic characteristics and the frequencies of point mutations in the patients using the Spearman test. Results. A total of 55 patients underwent direct analysis of the CYP21A2 gene in order to determine the presence of the 5 point mutations. Point mutations were identified in 31 patients, which corresponded to 56%. A statistically significant genotype-phenotype correlation was found. Conclusions. The correlation between the detected molecular defect and the clinical expression of 21OHD was reasonable in the Cuban population, which could allow phenotypic predictions to be made from the genotype.